Skin Manifestations in Dengue Patients of a Tertiary Hospital during Dengue Epidemic in Kathmandu: A Retrospective Study - Sitaula, Seema; Shrestha, Suraj; Mishra, Punam; Subba, Mamata; Poddar, Elisha (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Introduction: With a wide range of clinical manifestations and a drastic shift in epidemiology, dengue infection is a life-threatening condition. Studies of skin manifestations in dengue fever are scarce, and hence, it is prudent to explore the skin manifestations of dengue in Nepal for prompt diagnosis and to reduce associated complications. Methods: We conducted a single-center retrospective cross-sectional study from August 1, 2022, to December 1, 2022. Information on demographics, clinical characteristics of rash, and laboratory investigations were gathered in a pre-formed proforma from patients’ charts, which were organized and analyzed using the statistical software SPSS 21. Continuous data were presented as mean, and standard deviation and categorical data were presented as frequency and percentage. Results: There were 98 dengue cases with a mean age of 39.47 years. Among 43 patients, maculopapular (72.1%), erythematous macules (23.3%), purpuric (20.9%), both macules and maculopapular (11.6%) and ecchymotic (4.6%) rashes with no mucosal involvement were found. There was no statistically significant association between platelet count and rashes. Conclusion: Patients with dengue had varied cutaneous features. Maculopapular and erythematic rashes were the most commonly observed dermatological manifestations.